The Impact of the Coexpression of MET and ESR Genes on Prognosticators and Clinical Outcomes of Breast Cancer: An Analysis for the METABRIC Dataset - Nehad M. Ayoub; Ghaith M. Al-Taani; Amer E. Alkhalifa; Dalia R. Ibrahim; Aymen Shatnawi (The Breast Journal)
Purpose. Breast cancer is a heterogeneous disease. Exploring new prognostic and therapeutic targets in patients with breast cancer is essential. This study investigated the expression of MET, ESR1, and ESR2 genes and their association with clinicopathologic characteristics and clinical outcomes in patients with breast cancer. Methods. The METABRIC dataset for breast cancer was obtained from the cBioPortal public domain. Gene expression data for MET, ESR1, and ESR2, as well as the putative copy number alterations (CNAs) for MET were retrieved. Results. The MET mRNA expression levels correlated inversely with the expression levels of ESR1 and positively with the expression levels of ESR2 (r = −0.379, p<0.001 and r = 0.066, and p=0.004, respectively). The ESR1 mRNA expression was significantly different among MET CNAs groups p<0.001. Patients with high MET/ESR1 coexpression had favorable clinicopathologic tumor characteristics and prognosticators compared to low MET/ESR1 coexpression in terms of greater age at diagnosis, reduced Nottingham Prognostic Index, lower tumor grade, hormone receptor positivity, HER2-negative status, and luminal subtype p<0.001. In contrast, patients with high MET/ESR2 coexpression had unfavorable tumor features and advanced prognosticators compared to patients with low MET/ESR2 coexpression p<0.001. No significant difference in overall survival was observed based on the MET/ESR coexpression status. However, when data were stratified based on the treatment type (chemotherapy and hormonal therapy), survival was significantly different based on the coexpression status of MET/ESR. Conclusions. Findings from our study add to the growing evidence on the potential crosstalk between MET and estrogen receptors in breast cancer. The expression of the MET/ESR genes could be a novel prognosticator and calls for future studies to evaluate the impact of combinational treatment approaches with MET inhibitors and endocrine drugs in breast cancer.